Influence of cage fish farms in the dietary aspects at the individual level of a non-native fish species - Kliemann, Bruna Caroline Kotz [UNESP]; Delariva, Rosilene Luciana; Ramos, Igor Paiva [UNESP] (Springer Nature, 2024)
Given the influence of cage fish farms and the relevance of considering the inter-individual variation in the diet, we aimed to evaluate the dietary aspects of Geophagus sveni under the influence of cage fish farms in a neotropical reservoir at the individual level. To test the hypothesis that cage fish farms promote changes in the use of food resources at the individual level, we investigated the diet of two groups of G. sveni, one group under the influence of cage fish farms and another group without this influence. We observed that the group’s diet composition differed between the sampling areas due to the consumption of pelleted feed and reduced consumption of other items, such as invertebrates and plants, in the cage farm area. At the individual level, we observed specialist individuals in both sampling areas. This individual specialization may indicate that few individuals consumed a large volume of the pelleted feed, which was masked when assessing the group’s diet. We also observed that pelleted feed was an additional food item, and we suggest that this availability contributed to individual specialization in the cage farm area. In a general context, we also suggest that due to this supply of an additional highly energetic food item, cage fish farms may be favoring the success of the introduced species. Thus, we emphasize the need for individual evaluations in ecological studies, especially in assessing human-caused effects.
Keywords: Cultivation models; Diet; Geophagus sveni; Individual variation; Neotropical reservoir; Wild fish